Client-server, distributed database strategies in a health-care record system for a homeless population. - Chueh, H C (1994)
OBJECTIVE: To design and develop a computer-based health-care record system to address the needs of the patients and providers of a homeless population. DESIGN: A computer-based health-care record system being developed for Boston's Healthcare for the Homeless Program (BHCHP) uses client-server technology and distributed database strategies to provide a common medical record for this transient population. The differing information requirements of physicians, nurses, and social workers are specifically addressed in the graphic application interface to facilitate an integrated approach to health care. This computer-based record system is designed for remote and portable use to integrate smoothly into the daily practice of providers of care to the homeless. The system uses remote networking technology and regular phone lines to support multiple concurrent users at remote sites of care. RESULTS: A stand-alone, pilot system is in operation at the BHCHP medical respite unit. Information on 129 patient encounters from 37 unique sites has been entered. A full client-server system has been designed. Benchmarks show that while the relative performance of a communication link based upon a phone line is 0.07 to 0.15 that of a local area network, optimization permits adequate response. CONCLUSION: Medical records access in a transient population poses special problems. Use of client-server and distributed database strategies can provide a technical foundation that provides a secure, reliable, and accessible computer-based medical record in this environment.